Soil and Climate Characterization and Its Suitability for Nucleus Smallholder Oil Palm at Sei Pagar, Kampar District, Riau Province - I GEDE PUTU WIGENA; . SUDRADJAT; SANTUN R.P SITORUS; H. SIREGAR (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2009)
The management of nucleus smallholder oil palm after conversion is mostly improper with the promoted management practice, consequently oil palm yield decreases due to decreasing of land quality. For this reason, the study has been done to characterize land condition, to assess land suitability for oil palm and to correlate soil properties against oil palm yield. The study was conducted at Sei Pagar, Kampar District, Riau Province from January 2007 to March 2008. Soil erosion was estimated using Universal Soil Loss Equation, while land suitability was processed using Land Evaluation Technical Guidance for Agriculture Commodities, and correlation of soil  properties to oil palm yield was calculated using Multiple Regression Analysis on SPSS Version 12.0. The study showed that climate conditions was favorable for oil palm growth and production, with annual rainfall 2,339 mm year-1, air temperature 26.04oC, and relative humidity 81.2%. Soil erosion varied from 1.322-3.423 t ha-1 year-1. The soils were dominated by Typic Haplosaprist and Terric Haplosaprist covering 8,641 ha with land suitability of S2-f (moderately suitable with nutrients retention as limitng factor). The other soil are Humic Dystrudepts and Typic Dystrudepts covering 587 ha with land suitability of S2-f,n (moderately suitable with nutrients retention and nutrient supply as limiting factors). The soil properties of Typic Haplosaprist and Terric Haplosaprist affected to oil palm yield are organic-C, nitrogen content, P2O5 content, and available-S. Meanwhile, on Humic Dystrudepts and Typic Dystrudepts, oil palm yield was affected by organic-C, nitrogen content, available-S, and aluminum content.